Analysis of the Implementation of a Health Service Quality Monitoring Information System in Improving the Quality of Hospital Services - Esar Alkautsar; Eri Saputra; Rahmadi M. Ali (Universitas Malikussaleh, 2026)
Improving the quality of healthcare services is a top priority in hospital management. Utilizing information technology through a Healthcare Quality Monitoring Information System (HSMS) is a strategy that can be used to support the ongoing monitoring and evaluation of healthcare quality. This system enables more systematic, rapid, and accurate management of healthcare data, enabling the resulting information to be used as a basis for managerial decision-making. This study aims to examine the implementation of a Healthcare Quality Monitoring Information System and its impact on improving the quality of healthcare services in hospitals. The method used is a qualitative descriptive approach, with data collection through field observations, interviews with relevant parties, and analysis of supporting documents. The study focused on the effectiveness of the system, the quality of the information generated, ease of operation, and its contribution to improving healthcare performance. The results indicate that the use of a HSMS provides benefits in accelerating the process of monitoring quality indicators, facilitating the identification of service problems, and increasing the accuracy of decision-making based on available data. In addition, the system also supports efforts to increase patient satisfaction through more measurable service improvements oriented to user needs. However, several factors remain challenges in implementation, such as limited human resource capabilities, the need to improve user competency, and obstacles to data integration between departments within the hospital.